Analisis Risiko Nilai Tukar Mata Uang Asing Dengan Menggunakan Metode Value at Risk (VAR) Pada Bank Muamalat Indonesia - Yasinta Amalia, Nur; Rahmawati, Rafika (LPPM Universitas Islam 45, 2023)
This study aims to measure the maximum potential loss or VaR value for each type of Foreign Exchange based on the calculation results for 1 day, 5 days, and 20 days at Bank Muamalat Indonesia and determine the implementation of risk management applied by Bank Muamalat Indonesia to deal with foreign exchange risk. The research method in measuring Value at Risk of foreign exchange rates uses quantitative methods. The type of data that the author uses in this study is secondary time series data on foreign exchange rates of USD, JPY, EUR, and SAR at Bank Muamalat Indonesia. during the time period 2 January 2018 to 31 December 2018. Data analysis techniques in the study were carried out in several stages, namely calculating exchange rate returns, volatility and daily value at risk. The results showed that the maximum exchange rate risk borne in 1 day, 5 days and 20 days with a 95% confidence level. The implementation of underlying in foreign exchange transactions at Bank Muamalat Indonesia refers to the National Sharia Council regulation No.96 / DSN-MUI / IV / 2015 concerning Sharia Hedging Transactions (Al-Tahawwuth Al-Islami / Islamic Hedging) on Exchange Rates. Bank Muamalat has conducted hedging cooperation with PT Kharisma Pemasaran Bersama Nusantara (KPBN) or Indonesia Commodity (Inacom) on 05 December 2019 as a form of Foreign Exchange Rate risk management.